2019
DOI: 10.18203/issn.2454-5929.ijohns20194560
|View full text |Cite
|
Sign up to set email alerts
|

A study of the knowledge and attitude of physicians in the first aid management of epistaxis in Aseer region, Saudi Arabia

Abstract: <p class="abstract"><strong>Background:</strong> Epistaxis is the common occurrence of bleeding from the nose. It is usually noticed when blood drains out through the nostrils. There are two types: anterior (the most common), and posterior (less common, more likely to require medical attention). Sometimes in more severe cases, the blood can come up the nasolacrimal duct and out from the eye<span lang="EN-IN">. </span></p><p class="abstract"><strong>Methods:</s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Musleh et al found that the majority (88.5%) of the residents knew about the right position of patients with epistaxis. As for the first step to control bleeding, 60.6% of the residents gave the correct answer [ 21 ]. Abu‐Zaid et al found an awareness level of 72% among their study participants [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…Musleh et al found that the majority (88.5%) of the residents knew about the right position of patients with epistaxis. As for the first step to control bleeding, 60.6% of the residents gave the correct answer [ 21 ]. Abu‐Zaid et al found an awareness level of 72% among their study participants [ 22 ].…”
Section: Reviewmentioning
confidence: 99%